2020
DOI: 10.1108/md-09-2019-1296
|View full text |Cite
|
Sign up to set email alerts
|

Business model transformation toward sustainability: the impact of legitimation

Abstract: PurposeThis study aims to identify the legitimacy issues raised during a sustainable business model innovation, deployed by an Italian company, which was analyzed through the lens of the legitimation theory and the business model innovation theory.Design/methodology/approachA single case study methodology is employed for empirical research. Semistructured interviews, with top and middle management, were conducted together with the analysis of several internal and external documents, to corroborate the case ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 89 publications
1
43
0
1
Order By: Relevance
“…On this point, a further research gap emerges that academics may be interested in exploring in the future to investigate what drivers are needed to increase consumer and employee participation in CE processes. Previous studies clearly showed how legitimation is an essential driver in CE development (Biloslavo et al, 2020). The new insights coming from the practitioner side discuss the role of strategies for creating stakeholder engagement.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…On this point, a further research gap emerges that academics may be interested in exploring in the future to investigate what drivers are needed to increase consumer and employee participation in CE processes. Previous studies clearly showed how legitimation is an essential driver in CE development (Biloslavo et al, 2020). The new insights coming from the practitioner side discuss the role of strategies for creating stakeholder engagement.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, we believe our results could contribute to extending existing studies on CE. Although new technologies allow the development of new business models that allow the development of CE, the solutions provided still need to gain legitimation to be accepted (Biloslavo et al, 2020). Practical examples suggest that the development of stakeholder engagement could allow developing moral legitimacy (Reuber & Morgan‐Thomas, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Achieving legitimacy for local vertical-specific 5G services and service providers through the deployment of local 5G networks is, however, an open question in many countries. Indeed, disruptive innovations such as 5G have been found to cause regulatory, incumbent and social "pushbacks" and they can be expected also for vertical 5G services, as legitimacy is a precondition for successful value creation and capture on a technology (Biloslavo et al 2020).…”
Section: Business Perspectivementioning
confidence: 99%
“…Researchers agree that the contemporary European economy has faced new challenges due to the rapid technological advancement coupled with growing customer expectations (Biloslavo et al, 2020;Centobelli et al, 2020;Arnold et al, 2016). In the literature, the idea of Industry 4.0 is described as the fourth industrial revolution aimed at the production of technologically advanced products that meet customer expectations in terms of techniques, information technology and economy (Dos Santos et al, 2020;Xu et al, 2018;Piccarozzi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%